Pemimpin Non-Muslim Berdasarkan Sudut Pandang Al-Qur’an dan Hadis: Tinjauan Atas Pandangan Ja’far Umar Thalib - Taufik Akbar (Ushuluddin Faculty, PTIQ Institute, 2022)
The purpose of this article is to examine the beliefs of Ja'far Umar Thalib, a significant Islamic figure in Indonesia associated with the manhaj salaf movement and the founder of Laskar Jihad, which played a role in the conflict in Ambon, Maluku in 1999. Specifically, this article delves into Thalib's perspective on the leadership of non-Muslims and governments. To achieve this, the article employs a qualitative research approach using a netnographic character criticism research model. The study reveals that Thalib regards government leadership as a component of Islamic law in the field of as-siya>sah asy-syar’iyyah. Therefore, according to Thalib's viewpoint, a government leader must adhere to the Qur'an and hadith. Moreover, Thalib highlights the prohibition for Muslims to exhibit loyalty to non-believers, including Jews and Christians, especially when choosing a leader, based on QS. al-Maidah verse 51.